Diagnosis of fetal defects in twin pregnancies at routine 11–13‐week ultrasound examination. (6th March 2020) - Syngelaki, A.; Cimpoca, B.; Litwinska, E.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objectives: To examine the performance of the routine 11–13‐week scan in detecting fetal defects in twin pregnancies and to examine if, in pregnancies with a fetal defect, compared to those with normal fetuses, there is increased incidence of nuchal translucency thickness (NT) ≥ 95 th and ≥ 99 th percentiles or intertwin discordance in crown–rump length (CRL) ≥ 10% and ≥ 15%. Methods: This was a retrospective analysis of prospectively collected data in twin pregnancies undergoing routine ultrasound examination for fetal anatomy, according to standardized protocols, at 11–13 weeks' gestation between 2002 and 2019. Pregnancies with known chromosomal abnormality were excluded. The final diagnosis of fetal defect was based on the results of postnatal examination in cases of live birth and on the findings of the last ultrasound examination in cases of pregnancy termination, miscarriage or stillbirth. The performance of the 11–13‐week scan in the detection of fetal defects was determined. Results: The study population of 6366 twin pregnancies with two live fetuses at 11–13 weeks' gestation included 4979 (78.2%) dichorionic (DC) and 1387 (21.8%) monochorionic (MC) twin pregnancies. The main findings were: first, the overall incidence of fetal defects was higher in MC than in DC twins (2.8% vs 1.3%); second, the proportion of defects diagnosed in the first trimester was higher in MC than in DC twins (52.6% vs 27.1%); third, the pattern of defects in relation to detectability at the 11–13‐week scan (always detectable, sometimes detectable and never detectable) was similar to that reported previously in singleton pregnancies; fourth, always‐detectable defects included acrania, alobar holoprosencephaly, encephalocele, pentalogy of Cantrell, exomphalos, body‐stalk anomaly, twin reversed arterial perfusion sequence and conjoined twins; fifth, the incidence of fetal NT ≥ 95 th percentile was higher in those with than in those without a defect (16.5% vs 4.5% in DC twins and 19.2% vs 5.9% in MC twins) and this was also true for NT ≥ 99 th percentile (8.3% vs 1.0% in DC twins and 15.4% vs 2.0% in MC twins); and sixth, the incidence of CRL discordance ≥ 10% was higher in those with than in those without a defect (20.2% vs 7.9% in DC twins and 33.8% vs 9.3% in MC twins) and this was also true for CRL discordance ≥ 15% (10.1% vs 1.9% in DC twins and 28.2% vs 2.8% in MC twins). Conclusions: First, fetal defects are more common in MC than in DC twin pregnancies. Second, first‐trimester detection of fetal defects in DC twin pregnancies is similar to that in singleton pregnancies. Third, first‐trimester detectability of defects in MC twins is higher than in DC twins. Fourth, in twin pregnancies with a fetal defect, there is higher intertwin discordance in CRL and incidence of increased NT, but the predictive performance of screening by these markers is poor. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article has been selected for Journal Club. Click here to view slides and discussion points. This article‐s abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Diagnóstico de defectos del feto en embarazos de gemelos en el examen ecográfico de rutina de las 11–13 semanas Objetivos: Examinar la eficacia del examen rutinario de 11–13 semanas para detectar defectos fetales en embarazos de gemelos y examinar si, en los embarazos con un defecto fetal, en comparación con los de fetos normales, hay una mayor incidencia del grosor de la translucencia nucal (TN) ≥ percentil 95 o y ≥ percentil 99 o o una discordancia entre gemelos en la longitud céfalo‐caudal (LCC) ≥10% y ≥15%. Métodos: Este estudio fue un análisis retrospectivo de datos recogidos prospectivamente de embarazos de gemelos sometidos a exámenes ecográficos de rutina entre 2002 y 2019 para determinar la anatomía del feto, según protocolos estándar a las 11–13 semanas de gestación. Se excluyeron los embarazos con anomalías cromosómicas conocidas. El diagnóstico final de la anomalía fetal se basó en los resultados del examen posnatal en los casos de nacimientos vivos y en los hallazgos del último examen ecográfico en los casos de interrupción del embarazo, aborto o éxitus fetal. Se determinó la eficacia de la exploración de las 11–13 semanas en la detección de anomalías fetales. Resultados: La población de estudio fue de 6366 embarazos de gemelos con dos fetos vivos a las 11–13 semanas de gestación e incluyó 4979 (78, 2%) embarazos bicoriales (BC) y 1387 (21, 8%) monocoriales (MC). Los principales hallazgos fueron: primero, la prevalencia total de defectos fetales fue mayor en los gemelos MC que en los gemelos BC (2, 8% vs. 1, 3%); segundo, la proporción de defectos diagnosticados en el primer trimestre fue mayor en los gemelos MC que en los gemelos BC (52, 6% vs. 27, 1%); tercero, la pauta de defectos en relación con la detectabilidad en la exploración de 11–13 semanas (siempre detectable, a veces detectable y nunca detectable) fue similar a la reportada previamente para los embarazos con feto único; cuarto, entre los defectos siempre detectables estaban la acrania, la holoprosencefalia alobar, el encefalocele, la pentalogía de Cantrell, el onfalocele, la anomalía del pedículo embrionario, la secuencia de perfusión arterial inversa de los gemelos y los gemelos unidos; quinto, la frecuencia del percentil de la TN fetal ≥95 o fue mayor en los que tenían un defecto que en los que no lo tenían (16, 5% vs 4, 5% en los gemelos BC y 19, 2% vs 5, 9% en los gemelos MC) y esto también fue cierto para el percentil de la TN ≥99 o (8, 3% vs 1, 0% en gemelos BC y 15, 4% vs 2, 0% en gemelos MC); y sexto, la frecuencia de una discordancia de la LCC ≥10% fue mayor en los que tenían un defecto que en los que no lo tenían (20, 2% vs 7, 9% en los gemelos BC y 33, 8% vs 9, 3% en los gemelos MC) y esto también fue cierto para la discordancia de la LCC ≥15% (10, 1% vs 1, 9% en los gemelos BC y 28, 2% vs 2, 8% en los gemelos MC). Conclusiones: Primero, los defectos fetales son más comunes en embarazos de gemelos MC que en los de gemelos BC. Segundo, la detección en el primer trimestre de defectos fetales en los embarazos de gemelos BC es similar a la de los embarazos con feto único. Tercero, la detectabilidad en el primer trimestre de los defectos en los gemelos MC es mayor que en los gemelos BC. Cuarto, en los embarazos de gemelos con un defecto fetal, hay mayor discordancia entre los gemelos en la LCC y prevalencia de una mayor TN, pero la eficacia predictiva del cribado mediante estos marcadores es escasa. 摘要: 妊娠11‐13周常规超声检测中双胎胎儿缺陷诊断 目标: 审核评估妊娠11‐13周常规检测在双胎胎儿缺陷诊断中的表现，审核评估在发现胎儿缺陷的孕妇中，(对照正常胎儿)宫颈半透明厚度(NT)≥95%和≥99%或冠臀长(CRL)脐带缠络≥10%和≥15%的机率是否增加了。 方法: 这是一项根据标准协议，针对2002至2019年间妊娠11‐13周接受常规超声胎儿解剖学检测双胎孕妇的前瞻性收集数据回顾分析。排除了已知染色体异常的妊娠孕妇。胎儿缺陷最终诊断依据是(活产孕妇)产后检查结果，以及(终止妊娠、流产或死产孕妇)最后一次超声检查结果。明确了妊娠11‐13周检测在胎儿缺陷诊断中的表现。 结果: 研究对象为6366名双胎妊娠孕妇(两个为妊娠11‐13周活胎孕妇)，包括4979(78.2%)个双绒毛膜(DC)和1387(21.8%)个单绒毛膜(MC)双胎孕妇。主要研究结果:第一，MC双胎孕妇胎儿缺陷总发生率高于DC双胎孕妇(2.8%对 1.3%)；第二，孕早期MC双胎孕妇胎儿缺陷检出率高于DC双胎孕妇(52.6%对27.1%)；第三，妊娠11‐13周检测胎儿缺陷检出模式(总是可以检出、有时可以检出、总是无法检出)类似于之前报告的单胎妊娠检出模式；第四，总是可以检出的缺陷包括无颅、无前脑畸形、脑膨出、坎特雷尔五联症、脐凸出、体柄异常、胎动脉反向灌注综合征和连体双胞胎；第五，缺陷胎儿NT≥95%发生机率高于正常胎儿(DC双胎孕妇，16.5%对4.5%；MC双胎孕妇，19.2%对5.9%)，NT≥99%也是如此(DC双胎孕妇，8.3%对1.0%；MC双胎孕妇，15.4%对2.0%)；第六，缺陷胎儿CRL紊乱≥10%发生机率高于正常胎儿(DC双胎孕妇，20.2%对7.9%；MC双胎孕妇，33.8%对9.3%)，CRL紊乱≥15%也是如此(DC双胎孕妇，10.1%对1.9%；MC双胎孕妇，28.2%对2.8%)。 结论: 第一，相比DC双胎孕妇，MC双胎孕妇出现胎儿缺陷的机率更高。第二，DC双胎孕妇孕早期发现胎儿缺陷的机率与单胎妊娠相当。第三，MC双胎孕妇孕早期胎儿缺陷检出率高于DC双胎孕妇。第四，在检出胎儿缺陷的双胎孕妇中，CRL脐带缠络机率较高，NT增加机率较高，但基于这些标志物的筛检预测性能较差。